To evaluate the summation \(\sum_{i=1}^{12} \left(2i^2 - 7\right)\), we can break it down into two parts:
- Calculate \(\sum_{i=1}^{12} 2i^2\)
- Calculate \(\sum_{i=1}^{12} 7\)
Step 1: Calculate \(\sum_{i=1}^{12} 2i^2\)
First, we need to calculate \(\sum_{i=1}^{12} i^2\). There is a formula for the sum of squares:
\[ \sum_{i=1}^{n} i^2 = \frac{n(n+1)(2n+1)}{6} \]
For \(n = 12\):
\[ \sum_{i=1}^{12} i^2 = \frac{12(12+1)(2 \times 12 + 1)}{6} = \frac{12 \times 13 \times 25}{6} \]
Calculating this step-by-step:
\[ 12 \times 13 = 156 \]
\[ 156 \times 25 = 3900 \]
\[ \frac{3900}{6} = 650 \]
Thus,
\[ \sum_{i=1}^{12} i^2 = 650 \]
Now multiply this result by 2:
\[ \sum_{i=1}^{12} 2i^2 = 2 \times 650 = 1300 \]
Step 2: Calculate \(\sum_{i=1}^{12} 7\)
This is simply:
\[ \sum_{i=1}^{12} 7 = 7 \times 12 = 84 \]
Step 3: Combine the Results
Now we subtract the second summation from the first:
\[ \sum_{i=1}^{12} (2i^2 - 7) = 1300 - 84 = 1216 \]
Thus, the value of the summation is:
\[ \boxed{1216} \]